Ocular Tuberculosis Initially Presenting as Central Retinal Vein Occlusion. - Mahyudin, Muiz; Choo, May May; Ramli, Norlina Mohd; Omar, Sharifah S (2010)
A 23-year-old man presented with central retinal vein occlusion. The retinal haemorrhages worsened and signs of retinal vasculitis appeared later as vision dropped from 6/60 to Counting Fingers. No signs of systemic disease were observed. Routine Mantoux test and chest radiograph were negative for tuberculosis. Fundus flourescein angiogram confirmed presence of retinal vasculitis. Both systemic and topical corticosteroid therapy were ineffective. Polymerase chain reaction analysis of vitreous fluid showed presence of Mycobacterium tuberculosis. A full 6-month course of antituberculosis therapy was given and inflammation subsided. Vision improved to 3/60. This is a rare case of ocular tuberculosis without evidence of systemic infection, presenting first as a central retinal vein occlusion.